Conservation agrotechnology to improve soil quality and potato productivity Kuta Rayat Village, Naman Teran District, Karo Regency, North Sumatra - Rosmadelina Purba; Meriaty Meriaty; Ringkop Situmeang (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Potato production in North Sumatra is productive compared to other provinces with a yield of 124 326 tons in 2020. To continue to improve the quality and quantity of potato harvest each year, continuous innovation is needed in implementing agricultural systems and technologies that can increase productivity. This research aims to find agrotechnology that can increase productivity by focusing on developing the quality of soil as farming land in Kuta Rayat Village, Naman Teran District, Karo District, North Sumatra Province. Potato agrotechnology was studied through plot trials using the Randomized Block Design method with 7 treatments (agro-potato: mounds across the slope, quality seeds, lime dosage, manure and chemical fertilizer according to the recommendations given). Data collected included before and after treatment of soil properties and potato productivity. The results of this study showed that the dose of Dolomite lime 1.5 tons/ha, manure 20 tons/ha, 150 kg Urea, 150 kg ZA, 250 kg SP-36 and 200 kg KCl was sufficient to obtain optimal potato productivity and improve soil quality.